PENGARUH TANDEM GAIT EXERCISE TERHADAP PENINGKATAN KESEIMBANGAN PADA LANSIA DI POSYANDU LANSIA DESA KARANGPAKIS KECAMATAN KABUH KABUPATEN JOMBANG - Laili, Rosananda Astia Novia; Pradita, Agria; Zakaria, Amin; Fariz, Achmad (NHM PRESS, 2023)
Aging is part of the growth and development process, where major physiological changes occur, which impact on balance. Elderly people frequently develop balance abnormalities, which include issues with their walk, joint stiffness, and muscular weakness. Tandem gait exercise is an exercise performed by walking in a straight line with the heel touching the toe of the other foot at a distance of 3 to 6 meters with eyes open, this exercise is expected to balance in the elderly. The purpose of this study was to determine the effect of tandem gait exercise on improving balance in the elderly. This research is an experimental research with quasi experimental type and research design of one group pre test and post test. The samples of this study were 20 elderly people at the Posyandu Lansia Karangpakis, Kabuh, Jombang. In this study, Berg balance scale was used to measure balance and tandem gait exercise was used for physiotherapy intervention. The results of this study showed that the mean value before tandem gait exercise was 39 and the mean value after tandem gait exercise was 56. The results of the Wilcoxon test showed a p-value of 0.000 <0.05, which means that there is an effect on improving balance in the elderly after being given tandem gait exercise. Based on the results of this study, it can be concluded that tandem gait exercise can improve balance in the elderly.